Rastiščne značilnosti trajnih ploskev slovenske 16 x 16-kilometrske mreže - Urbančič, Mihej (Gozdarski vestnik, 2009)
This article presents the history of researches on the Slovenian 16 km x 16 kmnet, the purpose and the aim of the "BioSoil" demo project, pedological and phytocoenological work methods on the sites of the 16 x 16 km net, basic site data on locations and classification of soli of their representative soil profiles according to the Slovenian GIS and international WRB classification, and classification of their forest associations according to the habitat types.
Keywords: gozdovi; habitati; gozdna tla; gozdne združbe; rastlinske združbe; Slovenia; Slovenija